Insulin Enhances Migration and Invasion in Prostate Cancer Cells by Up-Regulation of FOXC2 - Sarkar, Phoebe L.; Lee, Wendy; Williams, Elizabeth D.; Lubik, Amy A.; Stylianou, Nataly; Shokoohmand, Ali; Lehman, Melanie L.; Hollier, Brett G.; Gunter, Jennifer H.; Nelson, Colleen C. (Frontiers in Endocrinology, 2019)
Androgen deprivation therapy (ADT) is the standard treatment in prostate cancer (PCa), yet many patients relapse with lethal metastatic disease. With the loss of androgens, increased cell plasticity is observed as an adaptive response to ADT. This includes gain of invasive and migratory capabilities, which may contribute to PCa metastasis. Hyperinsulinemia, which develops as a side-effect of ADT, has been associated with increased tumor aggressiveness and faster treatment failure. We investigated the direct effects of insulin in PCa cells that may contribute to disease progression. We measured insulin induced cell migration and invasion in vitro using wound healing and transwell assays in a range of PCa cell lines of variable androgen dependency (LNCaP, 22RV1, DUCaP and DU145 cell lines). Studies of molecular mechanisms driving insulin induced invasion was performed using microarray, quantitative real time-PCR and immunoblotting across three PCa cell lines. Insulin enhanced motility and invasiveness of PCa cells, upregulating FOXC2 and activating key PCa cell plasticity mechanisms including gene changes consistent with epithelial-to-mesenchymal transition (EMT) and development of a neuroendocrine phenotype. Additionally, analysis of publicly available clinical PCa tumor data showed associations of the key findings from our in vitro studies with metastatic prostate tumors demonstrating a positive correlation between insulin receptor expression and the EMT transcription factor FOXC2. As the insulin receptor is not clinically targetable, our data shows that actions of insulin in PCa cells may be suppressed with inhibitors to downstream signaling molecules, PI3K and ERK1/2. This study identifies for the first time, a mechanism for insulin-driven cancer cell motility and supports the concept that targeting insulin signaling at the level of the PCa tumor may extend the therapeutic efficacy of ADT.